Subclavian Artery Pseudoaneurysm Secondary to Accidental Stone Chip Injury and its Excision - Nagre, SW (Journal of Cardiovascular Medicine and Cardiology, 2016)
A pseudo aneurysm, also known as a false aneurysm, is a hematoma that forms as a result of a leaking hole in artery. Hematoma was contained by the surrounding tissues. Also it must continue to communicate with the artery to be considered a pseudo aneurysm. Post stab injury subclavian artery pseudoaneurysm is rare entity with great significance because of risk of complications like thrombosis, rupture, gangrene, limb loss and should be operated early whenever diagnosed. Our case report has 18 year male patient with history of accidental stone chip injury to left supraclavicular region followed by pulsatile swelling after five days due to subclavian artery pseudoaneurysm. We excised pseudoaneurysm with direct closure of opening in subclavian artery and removal of stone chip.